The NAM/ATAF1/2/CUC2 transcription factor PpNAC.A59 enhances PpERF.A16 expression to promote ethylene biosynthesis during peach fruit ripening. (1st October 2021) - Guo, Zhi-Hua; Zhang, You-Jia; Yao, Jia-Long; Xie, Zhi-Hua; Zhang, Yu-Yan; Zhang, Shao-Ling; Gu, Chao
Abstract: Peach is a typical climacteric fruit that releases ethylene during fruit ripening. Several studies have been conducted on the transcriptional regulation of ethylene biosynthesis in peach fruit. Herein, an ethylene response factor, PpERF.A16, which was induced by exogenous ethylene, could enhance ethylene biosynthesis by directly inducing the expression of 1-aminocyclopropane-1-carboxylic acid synthase ( PpACS1 ) and 1-aminocyclopropane-1-carboxylic acid oxidase ( PpACO1 ) genes. Moreover, the NAM/ATAF1/2/CUC2 (NAC) transcription factor (TF) PpNAC.A59 was coexpressed with PpERF.A16 in all tested peach cultivars. Interestingly, PpNAC.A59 can directly interact with the promoter of PpERF.A16 to induce its expression but not enhance LUC activity driven by any promoter of PpACS1 or PpACO1 . Thus, PpNAC.A59 can indirectly mediate ethylene biosynthesis via the NAC-ERF signaling cascade to induce the expression of both PpACS1 and PpACO1 . These results enrich the genetic network of fruit ripening in peach and provide new insight into the ripening mechanism of other perennial fruits.